2022
DOI: 10.1111/bjh.18192
|View full text |Cite
|
Sign up to set email alerts
|

The use of obinutuzumab and ofatumumab in the treatment of immune thrombotic thrombocytopenic purpura

Abstract: Immune thrombotic thrombocytopenic purpura (iTTP) is characterised by autoimmune mediated deficiency of ADAMTS13 (A disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13), with autoantibodies targeting ADAMTS13. Rituximab is a type I chimeric murine/human monoclonal antibody (mAb) against the CD20 molecule expressed on human B cells. The use of rituximab has been established for over a decade in the condition as an essential treatment modality to target the B-cell population producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…More recently, Ofatumumab and Obinutuzumab use has been reported by Doyle et al , 42 with treatment of 15 patients in 26 treatment episodes, ofatumumab ( n = 18) and obinutuzumab ( n = 8). In 21/26 cases, these agents were given as pre-emptive therapy to prevent a TTP relapse; in 12/15 cases, patients had previously developed serum sickness associated with rituximab.…”
Section: Use Of Elective Immunosuppressive Therapy To Prevent Ttp Rel...mentioning
confidence: 96%
See 2 more Smart Citations
“…More recently, Ofatumumab and Obinutuzumab use has been reported by Doyle et al , 42 with treatment of 15 patients in 26 treatment episodes, ofatumumab ( n = 18) and obinutuzumab ( n = 8). In 21/26 cases, these agents were given as pre-emptive therapy to prevent a TTP relapse; in 12/15 cases, patients had previously developed serum sickness associated with rituximab.…”
Section: Use Of Elective Immunosuppressive Therapy To Prevent Ttp Rel...mentioning
confidence: 96%
“…These agents were generally well tolerated, with 4/26 (15%) episodes of adverse events, comprising two infections and two atopic episodes. 42 …”
Section: Use Of Elective Immunosuppressive Therapy To Prevent Ttp Rel...mentioning
confidence: 99%
See 1 more Smart Citation
“…That is why the report by Doyle et al . showing the use of other anti‐CD20 monoclonal options in iTTP is an exciting study 1 . In this report it is shown that ofatumumab and obinutuzumab, both monoclonals with specificity to epitopes different from rituximab on CD20, can be effectively utilized in iTTP patients either not responding as expected or reacting adversely to rituximab.…”
mentioning
confidence: 89%
“…That is why the report by Doyle et al showing the use of other anti-CD20 monoclonal options in iTTP is an exciting study. 1 In this report it is shown that ofatumumab and obinutuzumab, both monoclonals with specificity to epitopes different from rituximab on CD20, can be effectively utilized in iTTP patients either not responding as expected or reacting adversely to rituximab. This report describes how these monoclonals were used as monotherapy pre-emptively if there was evidence of ADAMTS13 activity decrease or clinical suspicion of relapse, by either starting at lower test doses and then increasing them as tolerance to the medication was established or starting at a therapeutically appropriate larger dose while taking under consideration clinical need.…”
Section: Introductionmentioning
confidence: 96%